Pengaruh Disiplin Kerja Dan Peran Ganda Terhadap Kinerja Pegawai Wanita Pada PT. PLN Indonesia Power UBP Keramasan - Okta, Anti Amelia; Septayuda, Irwan (CV. ITTC INDONESIA, 2024)
The purpose of this study was to determine the effect of work discipline and dual roles on women’s performance at PT. PLN Indonesia Power UBP Keramasan. This study was conducted using quantitative methods obtained through interviews and research questionnaires. The sample in this study were 40. Female employees who were married. The results of this study indicate that the variables of work discipline and dual roles have a significant effect on the performance of female employees t count of 3.870 and a significance level of 0.003 for the work discipline variable. While the dual role variable t count is 3.070 and a significance level of 0.004. this means that there ia a significant influence between work discipline and dual roles on the performance of female employees.